Designing a CORBA-based high performance open programmable signaling system for ATM switching platforms. - Mun Choon Chan (IEEE Journal on selected areas in communications)
ATM switching platforms are well suited for transporting multimedia streams with quality-of-service (QOS) requirements. This paper describes the system design of a high performance connection management system for xbind, a flexible open programmable signaling system for ATM switching platforms. The latency and throughput of call processing is improved by caching, message aggregation, and processing of requests in parallel. Using a set of general purpose UNIX work stations, we are able to attain a maximum throughput of close to 600000 call operations/h (setup and delete) with an average call setup time of 85 ms. With a low traffic load of 3600 call operations/h, an average call setup latency of 11 ms can be obtained. The system is adaptive. By adjusting various control parameters, the connection manager(s) can be dynamically configured to trade off between throughput and call setup time